2011
DOI: 10.1371/journal.pone.0016385
|View full text |Cite
|
Sign up to set email alerts
|

The Cryptic African Wolf: Canis aureus lupaster Is Not a Golden Jackal and Is Not Endemic to Egypt

Abstract: The Egyptian jackal (Canis aureus lupaster) has hitherto been considered a large, rare subspecies of the golden jackal (C. aureus). It has maintained its taxonomical status to date, despite studies demonstrating morphological similarities to the grey wolf (C. lupus). We have analyzed 2055 bp of mitochondrial DNA from C. a. lupaster and investigated the similarity to C. aureus and C. lupus. Through phylogenetic comparison with all wild wolf-like canids (based on 726 bp of the Cytochrome b gene) we conclusively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
96
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(113 citation statements)
references
References 14 publications
11
96
0
6
Order By: Relevance
“…Previous authors have alternated between Canis lupaster (e.g., [13,14,38]) and Canis anthus [13]. Of these, C. anthus F. Cuvier, 1820 [10] has priority.…”
Section: Taxonomy and Nomenclaturementioning
confidence: 99%
See 3 more Smart Citations
“…Previous authors have alternated between Canis lupaster (e.g., [13,14,38]) and Canis anthus [13]. Of these, C. anthus F. Cuvier, 1820 [10] has priority.…”
Section: Taxonomy and Nomenclaturementioning
confidence: 99%
“…Recent publications [13][14][15] have identified this animal as a separate species, more closely related to the Holarctic grey wolf than to the golden jackal. Gaubert et al [13] suggested the existence of both the golden jackal and African wolf in North and West Africa.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The range of grey wolves and golden jackals overlaps in southern Asia, Middle East, and the Balkans, and no hybridisation studies were performed in the areas where these two species coexist. Some north African canids originally classified as golden jackals (C. aureus) were shown to carry mtDNA haplotypes falling within the grey wolf clade (Rueness et al 2011;Gaubert et al 2012). This was interpreted as a taxonomic misidentification, but could also result from hybridisation and introgression of grey wolf mtDNA into golden jackal populations; analysis of nuclear DNA is needed to clarify this.…”
Section: Hybridisationmentioning
confidence: 99%